Local Validation of G-ROP and Modified G-ROP Criteria in the Detection of Prethreshold Retinopathy of Prematurity - Jayvee S. Rivera, MD; Rachelle G. Anzures, MD, DPBO (Philippine Journal of Ophthalmology)
‎Objective: This study determined the diagnostic accuracies of Growth and Retinopathy of Prematurity (GROP) criteria and a novel modified G-ROP criteria on identifying retinopathy of prematurity (ROP) in infants referred for screening at a tertiary hospital.